Analisis Perspektif Konsumen Muslim di Wilayah Kabupaten Jember Terhadap Label Halal Produk Skincare Scarlett Dengan Menggunakan Theory of Planned Behavior - Dyah Islami; Shodiqin, Dimas Herliandis; Dhofir Catur Bashori; Nur, Siti Khayisatuzzahro (Intelektualitas Jurnal Penelitian Lintas Keilmuan, 2024)
Currently, there are many beauty and facial care products circulating in the midst of society. One of the beauty products that has gained a place in the midst of society is Scarlett products. This product is a very popular beauty product because of its outstanding quality. Scarlett is also registered with the Food and Drug Administration (BPOM) and has received Halal certification from MUI. This study aims to determine the perspectives, attitudes, subjective norms and behavioural control of Muslim consumers towards the halal label of Scarlett products. The research method used in this research is quantitative method. Data collection was carried out using a targeted sampling method through distributing questionnaires and interviews with 80 respondents. In this study, the data were analysed using regression coefficient test, multiple linear regression analysis, hypothesis test, and classical hypothetical test. The results showed that attitude affects the Halal label, while subjective norms do not affect the halal label, and consumer behaviour control affects the halal label for Scarlet products. According to this study, Muslim customers in Jember Regency should pay attention to halal labels on skin care products. In addition, future researchers are expected to test the formulation of the problem using different research methods or improve and add independent variables and dependent variables. In addition, providing more precise theories so that it is easier for readers to understand.